2014
DOI: 10.1111/jbi.12454
|View full text |Cite
|
Sign up to set email alerts
|

The influence of vagrant hosts and weather patterns on the colonization and persistence of blood parasites in an island bird

Abstract: Aim Colonization and extinction are important drivers of island biogeography, but they are difficult to study. We used a long‐term dataset to determine the mechanisms that contribute to colonization and persistence for vector‐borne blood parasites in an island population of birds that regularly receives infected vagrant conspecifics and wind‐assisted potential vectors from the mainland. Location Heron Island (Australia) and the Australian mainland. Methods We determined the prevalence, temporal stability and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…Only two co‐infections were observed for each of the above parasite pairs , despite each parasite occurring on all islands and habitats. Considering that H. zosteropis and H. killangoi are avian host specialists that appear restricted to Zosteropidae (Valkiūnas ; Clark & Clegg ), our results may be evidence of interspecific competition. We also found a striking difference in likelihoods of microfilaria co‐infection for the two Haemoproteus species.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Only two co‐infections were observed for each of the above parasite pairs , despite each parasite occurring on all islands and habitats. Considering that H. zosteropis and H. killangoi are avian host specialists that appear restricted to Zosteropidae (Valkiūnas ; Clark & Clegg ), our results may be evidence of interspecific competition. We also found a striking difference in likelihoods of microfilaria co‐infection for the two Haemoproteus species.…”
Section: Discussionmentioning
confidence: 73%
“…Eight known co‐infections produced Haemoproteus sequences, while a further six produced double peaks (re‐sequencing of all six producing clean Plasmodium sequences). Haemoproteus lineages were therefore characterized using genus‐specific primers designed from sequences recovered in Australasian hosts (Clark & Clegg ; Clark, Clegg & Klaassen ). These primers successfully amplified Haemoproteus DNA from all visually observed Plasmodium / Haemoproteus co‐infections.…”
Section: Methodsmentioning
confidence: 99%
“…Members of the Zosterops spp. Haemoproteus clade are within 1–3% nucleotide divergence of ZOSLAT04H, a lineage reported in Australian Z. lateralis that has been microscopically confirmed as the Zosteropidae‐restricted Haemoproteus zosteropis (Clark & Clegg ). In contrast, lineages from the second Haemoproteus clade averaged over 5% nucleotide divergence from lineages in the Zosterops spp.…”
Section: Discussionmentioning
confidence: 73%
“…A more complete description of the parasite communities and genetic connectivity of numerous host and vector species would be required to establish whether a relationship exists, and if so, to determine whether parasite community is shaped by movement patterns of hosts, or whether gene flow patterns of hosts are shaped by parasite community incompatibilities. In one population of silvereyes ( Zosterops lateralis chlorocephalus ) on Heron Island on the southern Great Barrier Reef of Australia, a combination of empirical infection data and simulations showed that the arrival of parasites via mainland vagrant silvereyes was not consistent with parasite community patterns in the island bird population, and instead, vector movement was a likely influence (Clark & Clegg ).…”
Section: Discussionmentioning
confidence: 99%
“…Although island biogeography of parasites and their colonization histories have received increasing attention in recent years (e.g. Cornuault et al , 2012; Sari et al , 2013; Clark & Clegg, 2015), studies thus far have investigated the effects of insularity on parasite diversity and phylogenetic relationships on islands only (Ishtiaq et al , 2012; Carlson et al , 2013; Olsson-Pons et al , 2015; Ricklefs et al , 2016), or have compared islands with the mainland but taking into consideration only one host species (Pérez-Rodríguez et al , 2013; Sari et al , 2013). It is therefore of interest to test if the core predictions of island biogeography theory apply to parasite communities on a broader scale, i.e.…”
Section: Introductionmentioning
confidence: 99%